Peningkatan Hasil Belajar Tematik Terpadu Peserta Didik Menggunakan Model Discovery Learning di Kelas V Sekolah Dasar - Suryani, Mesi; Suriani, Ari (Universitas Negeri Padang, 2024)
This study aims to describe the use of the Discovery Learning model in Class VA. This type of research is Classroom Action Research with four stages: planning, implementing, observing and reflecting using qualitative and quantitative approaches. The subjects were teachers and VA class students, totalling 27 students, there were 17 female students and 10 male students. From the results of the RPP research in cycle I obtained qualifications (B) then in cycle II obtained qualifications (SB). In the first cycle, the assessment of teacher activity obtained qualifications (B) increased in cycle II (SB). In cycle I, the evaluation of student activity qualifications (B) increased in cycle II with qualifications (SB). assessment of student learning outcomes in cycle I obtained predicate (C) and cycle II obtained predicate (B). It can be concluded that the Discovery Learning model can improve student learning outcomes in integrated thematic learning in grade V Elementary School.